EATING DISORDERS IN YOUNG PEOPLE WITH PREDIABETES - Алексеева, Наталья Сергеевна (Medicine in Kuzbass, 2022)
Purpose of the study – to evaluate eating disorders in young individuals with prediabetes mellitus. Materials and Methods. A randomized study was conducted among 89 patients with prediabetes (64 % (n = 57) women, 36 % (n = 32) men) aged 30 to 45 years, with a metabolic phenotype. The control group consisted of 65 healthy volunteers (61.5 % (n = 40) women, 38.5 % (n = 25) men) aged 29 to 44 years, without prediabetes and metabolic syndrome components, with normal body weight. Eating behavior typologies were determined using DEBQ questionnaires. Results. In the presence of prediabetes there were registered disorders of clinical and metabolic status (abdominal obesity, insulin resistance, systemic inflammation, hyperlipidemia). When analyzing eating behavior, it was found that these disorders occurred more frequently in pre-diabetes patients (74.1 %, n = 66) than in controls (21.5 %, n = 14, p < 0.001). Emotional (34.8 %, n = 31) and externalizing types of eating disorders (28.1 %, n = 25) predominated in pre-diabetic patients. The restrictive type of eating behavior was represented almost equally in both prediabetes patients (11.2 %, n = 10) and controls (9.2 %, n = 6, p = 0.688). Individuals with NTG were also found to be more stressed and emotionally distressed than those with NGN. The emotiogenic type of eating disorder was prevalent in individuals with NTG (46.4 %, n = 20), as opposed to young adults with NGN (23.9 %, n = 11, p = 0.026). Conclusion. Prediabetes is a potentially reversible condition compared with DM2. Therefore, active preventive measures aimed at the diagnosis and correction of eating disorders, especially of the emotiogenic type, will be important for the prevention of both prediabetes at a young age and further development of CVD in this category of individuals.